Assessment of solar panel contamination via its image in Libya climate - A. A. Albagoush; A. B. Kupriyanov (Системный анализ и прикладная информатика)
Modern solar power plants are usually built in deserts, in conditions of lack of water and a lot of dust. Dustiness of solar panels leads to a decrease in their efficiency, and cleaning the panels from dust is an energy consuming operation. The article discusses an approach to assessing the degree of contamination of a panel and making a decision about the need to clean it based on analysis of the panel image. An algorithm for making a cleaning decision is presented, a software application for assessing the degree of contamination of the panel is described, and the results of an experimental test of the created application are presented.